Sung-Wook Moon, Rutebeuf ou une écriture du « divers » - Sung-Wook Moon (Perspectives Médiévales)
Rediscovered for two centuries, Rutebeuf now has the status of a great poet of the Middle Ages. This reputation, however, had the side effect of discouraging the effort to revisit his work on a fresh basis. Also his polygraphy, going back and forth between fabliau and hagiography, satire of the world and self-mockery, impelled critics sometimes to distribute his fifty or so poems into different categories that have little to do with each other, sometimes to favour this or that group of texts to the detriment of the others. Examining the existing scientific achievements, as in the literary and philological field as in terms of historiography, and confronting new questions stimulated by poetry more subtle than has often been believed, this study has ambition to restitute to the medieval writer a writing conscious of its powers and its weaknesses, writing elaborated in contact and dealing with history and current affairs, reflecting on the relationship between his ineluctably fabulous language and the reality of the world he lives, not without drawing some audacious claims about the merits specific to his labour. The unity of Rutebeuf’s work results of the constancy of the interrogation running through it. In that way, this person even whose real name remains unknown appears as a subject, identical to himself in the diversity of his acts, acts that he attributes to his own credit and of which he takes the whole responsibility.